PENGARUH PEMBIAYAAN PLS DAN NON-PLS TERHADAP KINERJA BANK SYARIAH DI INDONESIA - Mubarok, Alrojak; Yasin, Ach. (Universitas Negeri Surabaya, 2025)
This study aims to analyze the effect of Profit and Loss Sharing (PLS) and Non-PLS-based financing on the performance of Islamic banks in Indonesia. The background of this study is based on the dominance of Non-PLS contracts, especially murabahah, in Islamic bank financing portfolios, although PLS contracts are considered more ideal in accordance with sharia principles. The study uses a quantitative approach with a multiple linear regression method. Secondary data were obtained from the monthly financial reports of Islamic banks for the period 2019–2024 published by the Financial Services Authority (OJK). The results show that PLS financing has no significant effect on Islamic bank performance, while Non-PLS financing is proven to have a positive and significant effect on bank profits. Simultaneously, both types of financing have a significant effect on Islamic bank performance with a coefficient of determination of 0.916, meaning that 91.6% of the variation in bank performance can be explained by PLS and Non-PLS financing. This finding indicates that although PLS is in accordance with the principles of sharia justice, the dominant contribution to Islamic bank profitability still comes from Non-PLS financing.